Antecedents And Consequences Of Tourist Satisfaction: A Literature Review - Adinegara, Joko; Suprapti, Ni Wayan Sri; Yasa, Ni Nyoman Kerti; Sukaatmadja, I Putu Gde (ASEAN Marketing Journal, 2021)
The concept of satisfaction is being practiced worldwide at very large scale and has drawn significant attention from academics and practitioners, because it played an important role in company marketing strategies and it was recognized as driving force of loyalty. Although the antecedent of satisfaction was widely learned, the antecedent of satisfaction is still debate by the researcher. The aim of this article is to develop more integrative constructs of satisfaction and its consequences and how the correlations among constructs that form the satisfaction. By understanding the factors that form the satisfaction and its consequences, is expected to be composed of a marketing strategy that can be implemented in an effort to increase the satisfaction and loyalty of tourist destinations. This article also gives direction for future study and managerial pointers for setting up a construct of satisfaction.